Reverse Logistics: Overview and Challenges for Supply Chain Management. (21st July 2014) - Rubio, Sergio; Jiménez-Parra, Beatriz
This paper is aimed at introducing the concept of reverse logistics (RL) and its implications for supply chain management (SCM). RL is a research area focused on the management of the recovery of products once they are no longer desired (end-of-use products, EoU) or can no longer be used (end-of-life products) by the consumers, in order to obtain an economic value from the recovered products. This way, RL has become a matter of strategic importance, an element that companies are considering in their decision-making processes related to the design and development of their supply chains. In addition, a description of the implications of RL for SCM will be discussed and, finally, an analysis of some of the opportunities and challenges that RL implies for SCM will be presented.